THE ROLE OF TEACHER AND CURRICULUM IN INTERVENTIONS IN DAILY LESSONS - KIM, Ok-kyeong (The Eurasia Proceedings of Educational and Social Sciences, 2015)
The demand of interventions in daily lessons is high in the classroom, and curriculum programs make an effort to include resources for such interventions. Yet, there is no clear theoretical and practical guidance on daily interventions for both teacher and curriculum. This study examines interventions that are offered in written lessons from a range of elementary mathematics curriculum programs and those that teachers actually incorporate into instruction, aiming at understanding the nature of interventions embedded in daily lessons and the role of teacher and curriculum in classroom interventions. The results of the study highlight the importance of intervention resources in the curriculum and teacher role in recognizing the affordances of resources to provide appropriate interventions toward the mathematical point of the lesson.